SURVEI DAN TINJAUAN GEOTEKNIK TERHADAP KERUSAKAN BANGUNAN DAN KELONGSORAN PASCA GEMPA CIANJUR 2022 - Pinondang Simanjuntak; Efendy Tambunan; Candra Christianti Purnomo; Clijster Annayetty Mamoribo; Goklas Pandaraman Sihombing; Edward Gultom; Adriana Vania; Lolom Evalita Hutabarat (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
An earthquake magnitude of 5.6 on the SR rocked Cianjur Regency, West Java Province, on Monday, 21 November 2022, at 13.21 WIB. The earthquake caused damage to residential buildings and caused landslides in vital and densely populated areas. The fault that occurred on the eastern plateau in Sarampad Village was in the form of a relatively long shift in land. Physical land shifts due to faults can be seen from shifts in Sarampad Village, where the huts in the fields have moved very far from their original position. Likewise, landslides occurred in the horseshoe area of the national road between Cianjur City and Puncak, with the slope of the surrounding landslide being quite steep on the upper slope of the highway and continuing down the slope on the side of the highway leading to the river below the surface of the road. The existence of a river indicates a layer of water close to the surface of the land used by the community and army dormitories near that location. This condition causes the soil to become saturated with water, making it a factor that causes landslides quickly if an earthquake occurs. Landslides on the ridge above the highway have been strengthened with stone gabion reinforcements placed with a terracing system. Meanwhile, the landslides under the highway have not been reinforced. Also, faults that occur on road sections transversely on the road body close to the horseshoe with curved contours need to be handled seriously